The usability of climate information in sub-national planning in India , Kenya and Uganda: the role of social learning and intermediary organ isations - Fisher, Susannah; Dodman, David; Epp, Marissa Van; Garside, Ben (Climatic Change, 2018)
Abstract Research on using climate information has often focused on th e interaction between users and producers and the technical fit of inf ormation for real decision-making. However, due to resource and capaci ty constraints within both user and producer communities, this approac h will not always be feasible or indeed necessary depending on the dec isions at hand. These contexts have been relatively under-explored by scholars, and this paper provides an original empirical contribution u sing three case studies of sub-national governments in India, Kenya an d Uganda. In the paper, we analyse how social learning supports changi ng the usability of climate information and the role of intermediary o rganisations in these processes. Firstly, the paper shows that interme diaries often choose to build the commitment to project aims rather th an using climate information as an entry point to working on climate c hange, and this allows them to instigate challenging learning processe s. Secondly, there are barriers to iterative processes and critical re flection with government stakeholders but these processes can gain tra ction when built into institutional practices such as formal M&E proce sses. Lastly, social learning can broaden the framing of climate chang e from a single sector issue to a multi-sectoral one. We conclude by a rguing that bringing together scholarship on social learning with that on the usability of climate information can deepen understanding of t he dynamic context in which the information becomes usable. The eviden ce from the case studies shows that learning processes can alter this context across scales.